2010
DOI: 10.1088/0268-1242/25/6/065009
|View full text |Cite
|
Sign up to set email alerts
|

Photoreflectance and photoluminescence study of annealing effects on GaAsBi layers grown by metalorganic vapor phase epitaxy

Abstract: The optical properties of GaAsBi layers grown by atmospheric pressure metalorganic vapor phase epitaxy on p-type GaAs substrates and annealed at different temperatures are investigated by photoreflectance and photoluminescence spectroscopies. Photoreflectance spectra show no significant shift in the band gap energy of GaAs 0.965 Bi 0.035 with annealing temperature except 600 • C for which the band gap energy reaches a minimum value corresponding to a red shift of 60 meV. The low temperature photoluminescence s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 25 publications
2
33
0
Order By: Relevance
“…There are a number of annealing studies reported and they are summarized in Table 5 below. Most previous reports focus on RTA of GaAsBi grown by both MBE [141,[143][144][145][146][147] and MOCVD [148,149]. The growth temperature used is between 200 and 420 • C measured by a thermocouple.…”
Section: Thermal Stability and Bi Diffusionmentioning
confidence: 99%
See 3 more Smart Citations
“…There are a number of annealing studies reported and they are summarized in Table 5 below. Most previous reports focus on RTA of GaAsBi grown by both MBE [141,[143][144][145][146][147] and MOCVD [148,149]. The growth temperature used is between 200 and 420 • C measured by a thermocouple.…”
Section: Thermal Stability and Bi Diffusionmentioning
confidence: 99%
“…Post-growth RTA is performed at 500-900 • C for a typical duration of 30-900 sec. The most common assessment methods are HRXRD and PL, while other methods like time-resolved PL [144,146] and PR [149] are sometime used.…”
Section: Thermal Stability and Bi Diffusionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chine et al have studied the effects of annealing on the photo-reflectance and photoluminescence for GaAsBi layers grown by metal-organic vapor phase epitaxy [9]. They reported that PL measurements below 100 K show a new large band centered at 1.36 eV and depends strongly on bismuth flow.…”
Section: Effects Of Thermal Annealing On the Spectral Properties Of Gmentioning
confidence: 99%